Densification and Thermal Stability of Hot‐Pressed Si3N4–ZrB2 Ceramics. Issue 12 (6th October 2015) - Guo, Wei‐Ming; Gu, Shang‐Xian; You, Yang; Jiang, Qiang‐Guo; Wu, Shang‐Hua; Lin, Hua‐Tay
Abstract : Densification and thermal stability of hot‐pressed Si3 N4 –ZrB2 ceramics with and without additives were investigated in N2 atmosphere. The addition of MgO–Yb2 O3, MgO–Y2 O3, and Al2 O3 –Yb2 O3 resulted in significant increase in relative density of the ceramics hot‐pressed at 1500°C from 48.5% to 98.0%, 97.3%, and 95.6%, respectively. There was weak reaction of ZrB2 with N2 to form ZrN in hot‐pressed ceramics. Then heat treatment at 1550°C resulted in the further reactions to produce ZrN, ZrSi2, and BN. The Si3 N4 –ZrB2 ceramics with MgO–Yb2 O3 showed much better thermal stability as compared to the ceramics with Al2 O3 –Yb2 O3 . The small difference in density led to the obvious difference in thermal stability. Therefore, Si3 N4 –ZrB2 ceramics should be densified to full density, to obtain high thermal stability.